MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN MELALUI MEDIA PAPAN BILAH BAGI ANAK TUNAGRAHITA RINGAN - Maisy Murni (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : This research is motivated by the problems that appear in the field that is a mild mental retardation child class DIII/C in SLB Limas Padang who have difficulty in doing the sum of numbers that the result is less than 20. Under these conditions, this study aims to demonstrate the use of media in the slats board increase ability summation of numbers that the result is less than 20 for mild mental retardation child class DIII/C in SLB Limas Padang. This study uses the Single Subject Research approach with ABA design. Subjects were mild mental retardation child class DIII / C. Baseline conditions (A1) is the ability of a child early in the sum of numbers that the result is less than 20 before being given treatment, intervention condition (B) is a condition in which a child is given the treatment by the media board slats, while the baseline condition (A2) is not given the ability of the child after treatment again. Target behaviors in this study is the child able to work on the problems that result is the sum of numbers less than 20, as measured by percentage. Techniques of data analysis in this study is the use of visual analysis chart. Kata Kunci: Anak Tunagrahita Ringan; Penjumlahan Bilangan yang hasilnya 20 kebawah ; Media Papan Bilah.